Enhancing the Performance and Stability of Li-CO2 Batteries Through LAGTP Solid Electrolyte and MWCNT/Ru Cathode Integration - Dan Na; Dohyeon Yu; Hwan Kim; Baeksang Yoon; David D. Lee; Inseok Seo (Nanomaterials)
Li-CO2 batteries (LCBs) have emerged as promising solutions for energy storage, with the added benefit of contributing to carbon neutrality by capturing and utilizing CO2 during operation. In this study, a high-performance LCB was developed using a Ge-doped LiAlGeTi (PO4)3 (LAGTP) solid electrolyte, which was synthesized via a solution-based method by doping Ge into NASICON-type LATP. The ionic conductivity of the LAGTP pellets was measured as 1.04 × 10−3 S/cm at 25 °C. The LCB utilizing LAGTP and an MWCNT/Ru cathode maintained a stable cycling performance over 200 cycles at a current density of 100 mA/g, with a cut-off capacity of 500 mAh/g. Post-cycle analysis confirmed the reversible electrochemical reactions at the cathode. The integration of LAGTP as a solid electrolyte effectively enhanced the ionic conductivity and improved the cycle life and performance of the LCB. This study highlights the potential of Ge-doped NASICON-type solid electrolytes for advanced energy-storage technologies and offers a pathway for developing sustainable and high-performance LCBs.